2002
DOI: 10.1590/s0100-29452002000300020
|View full text |Cite
|
Sign up to set email alerts
|

Características pós-colheita de frutos de genótipos de bananeira (Musa spp.)

Abstract: O conhecimento das características pós-colheita de novos híbridos de bananeira é uma importante informação que auxilia o melhorista em sua tomada de decisão. Este trabalho teve como objetivo avaliar genótipos de bananeira com relação às características de pós-colheita e resistência ao desprendimento do fruto. Foram utilizados frutos da segunda penca de 16 híbridos (Calipso, Bucaneiro, Ambrosia, YB42-21, PV42-53, PV42-68, PV42-81, PV42-85, PV42-129, PV42-142, PV42-143, ST12-31, ST42-08, PV03-44, FHIA-03 e SH 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1
22

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 2 publications
1
2
1
22
Order By: Relevance
“…This occurs because soluble solids, which are formed mainly of sugars, are the primary responsible for the formation of different osmotic potentials between the flesh and the peel (ADÃO & GLÓRIA, 2005). The averages obtained in the experiment were between 1.35 and 2.86, similar to the numbers reported by CERQUEIRA et al (2000), and expressing good flesh yield. With regard to color, at the beginning of the experiment all fruits were in color 01 (completely green), according to subjective visual rating scale used (Table 5).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…This occurs because soluble solids, which are formed mainly of sugars, are the primary responsible for the formation of different osmotic potentials between the flesh and the peel (ADÃO & GLÓRIA, 2005). The averages obtained in the experiment were between 1.35 and 2.86, similar to the numbers reported by CERQUEIRA et al (2000), and expressing good flesh yield. With regard to color, at the beginning of the experiment all fruits were in color 01 (completely green), according to subjective visual rating scale used (Table 5).…”
Section: Resultssupporting
confidence: 77%
“…However, the treatments used induced a great variation of soluble solids when compared to the results obtained by CERQUEIRA et al (2000) and MATSUURA et al (2004), which used 'Nanica' banana and resulted in averages between 22.9% and 28.3%, while the results of the present experiment ranged from 8% to 17.75% on average, and it may indicate that the fruit did not complete their maturation within the evaluation time, since they were not air conditioned. JUNQUEIRA et al (2004), working with nonconditioned fruits, found that treatments containing soybean oil controlled fruit ripening well in comparison to the control, finding values of solid contents in the fruits between 13.5 and 8.25% after 15 days of storage, which are lower than those observed in untreated fruits.…”
Section: Resultscontrasting
confidence: 69%
“…De modo geral, esses valores foram superiores aos encontrados por Cerqueira et al (2002), os quais trabalharam com diferentes híbridos e cultivares de bananeiras. Damatto Junior et al (2005) também avaliaram a relação polpa/casca dos cultivares Prata Anã e Prata Zulu, encontrando valores de 1,81 e 3,43, respectivamente.…”
Section: Resultsunclassified
“…Valores médios dos ciclos de produção (CP), altura de plantas na colheita (ALPC), perímetro do pseudocaule na colheita (PPCC), número de folhas vivas por planta (NFVP), massa da matéria fresca do cacho (MMFC), número de pencas por cacho (NPCA), número de frutos por cacho (NFCA), massa da matéria fresca da 2ª penca (MMFSP), número de frutos da 2ª penca (NFSP), comprimento de frutos (CF), diâmetro de frutos (DF), relação polpa casca (RPC) e firmeza (FIR) de frutos da bananeira 'Prata Anã' no 1° e 2° ciclo de produção, no Submédio São Francisco. Cerqueira et al (2002) avaliaram 16 híbridos e quatro cultivares, dentre os quais a 'Prata Comum' e o híbrido da 'Prata Anã' (SH 3640), sendo verificados, para a acidez titulável, valores de 0,52 e 0,48% de ácido málico e, para a relação SS/AT, valores de 44,72 e 40,22, respectivamente, índices próximos, portanto, aos encontrados no primeiro ciclo (49,42), porém, acima daqueles do segundo (34,40), sendo que os valores de AT encontrados no segundo ciclo, neste trabalho, foram superiores aos encontrados por Matsuura et al (2002), para a 'Pacovan' (0,64% de ácido málico), a qual, normalmente, apresenta frutos mais ácidos.…”
Section: Resultsunclassified
“…Frutos de 'Thap Maeo' apresentaram SS de 24,05 %, maior AT (0,55 %) e pH (4,20). Cerqueira et al (2002), em Cruz das Almas-BA, observaram que 'Tropical' apresentou frutos com firmeza de 28,0 N, SS 19,44 ºBrix e AT 0,48 %. Os frutos de 'Nam' foram mais doces (21,10 ºBrix), menos ácidos (0,19 %) e menos firmes (24,80 N).…”
Section: (Recebido Em 11 De Julho De 2008 E Aprovado Em 19 De Março Dunclassified